FEATURES OF TOPOGRAPHIC ANATOMICAL AND MORPHOLOGICAL CHANGES OF TMJ ELEMENTS IN PATIENTS WITH UNILATERAL AND BILATERAL DISPOSITION OF ARTICULAR DISK ACCORDING TO MRI SCAN - Yu. S. Lunkova; Yu. V. Stupina; V. M. Novikov (Український стоматологічний альманах)
Temporomandibular joint (TMJ) disorders are found in 37-67% of dental patients and take a leading position among maxillofacial diseases. TMJ disorders are more common in woman than in man (ratio is 8,4 :1 respectively).